Neurobehavioral phenotyping of Gαq knockout mice reveals impairments in motor functions and spatial working memory without changes in anxiety or behavioral despair - Frederick, Aliya L.; Saborido, Tommy P.; Stanwood, Gregg D. (Frontiers in Behavioral Neuroscience, 2012)
Many neurotransmitters, hormones and sensory stimuli elicit their cellular responses through the targeted activation of receptors coupled to Gq family heterotrimeric G proteins. Nevertheless, we still understand little about the consequences of loss of this signaling activity on brain function. We therefore examined the effects of genetic inactivation of Gnaq on responsiveness in a battery of behavioral tests in order to assess the contribution of Gaq signaling capacity in the brain circuits mediating expression of affective behaviors (anxiety and behavioral despair), spatial working memory and locomotor output (coordination, strength, spontaneous activity and drug-induced responses). First, we replicated and extended findings showing clear motor deficits in Gaq knockout mice as assessed on an accelerating rotarod and the inverted screen test. We then assessed the contribution of the basal ganglia motor loops to these impairments, using open field testing and analysis of drug-induced locomotor responses to the psychostimulant cocaine, the benzazepine D1 receptor agonists SKF83822 and SKF83959, and the NMDA receptor antagonist MK-801. We observed significant increases in drug-induced locomotor activity in Gaq knockout mice from the dopaminergic agonists but not MK-801, indicating that basal ganglia locomotor circuitry is largely intact in the absence of Gaq. Additionally, we observed normal phenotypes in both the elevated zero maze and the forced swim test indicating that anxiety and depression-related circuitry appears to be largely intact after loss of Gnaq expression. Lastly, use of the Y-maze revealed spatial memory deficits in Gaq knockout mice, indicating that receptors signaling through Gaq are necessary in these circuits for proficiency in this task.